2017
DOI: 10.1093/hmg/ddx216
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial deficits and abnormal mitochondrial retrograde axonal transport play a role in the pathogenesis of mutant Hsp27-induced Charcot Marie Tooth Disease

Abstract: Mutations in the small heat shock protein Hsp27, encoded by the HSPB1 gene, have been shown to cause Charcot Marie Tooth Disease type 2 (CMT-2) or distal hereditary motor neuropathy (dHMN). Protein aggregation and axonal transport deficits have been implicated in the disease. In this study, we conducted analysis of bidirectional movements of mitochondria in primary motor neuron axons expressing wild type and mutant Hsp27. We found significantly slower retrograde transport of mitochondria in Ser135Phe, Pro39Leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 65 publications
0
35
0
1
Order By: Relevance
“…In the experiments of Kalmar and colleagues on cultured motor neurons, the expression of HSPB1 mutants, most remarkably p.S135F, decreased mitochondrial membrane potential in neurites and impaired complex I activity [360]. This was accompanied with decreased glutathione levels and increased oxidative stress [360]. As the retrograde transport of p75NTD was affected to a lower extent, a primary impairment in mitochondrial function, rather than a cytoskeletal defect, was suggested to underlie the altered mitochondrial transport in this model [360].…”
Section: Downstream Pathomechanismsmentioning
confidence: 93%
See 3 more Smart Citations
“…In the experiments of Kalmar and colleagues on cultured motor neurons, the expression of HSPB1 mutants, most remarkably p.S135F, decreased mitochondrial membrane potential in neurites and impaired complex I activity [360]. This was accompanied with decreased glutathione levels and increased oxidative stress [360]. As the retrograde transport of p75NTD was affected to a lower extent, a primary impairment in mitochondrial function, rather than a cytoskeletal defect, was suggested to underlie the altered mitochondrial transport in this model [360].…”
Section: Downstream Pathomechanismsmentioning
confidence: 93%
“…This was accompanied with decreased glutathione levels and increased oxidative stress [360]. As the retrograde transport of p75NTD was affected to a lower extent, a primary impairment in mitochondrial function, rather than a cytoskeletal defect, was suggested to underlie the altered mitochondrial transport in this model [360]. One mechanism for this was identified by Schwartz et al, who showed that an abnormal interaction of mutant HSPB1 with ceramide synthase led to decreased mitochondrial ceramide content and impaired respiration [362].…”
Section: Downstream Pathomechanismsmentioning
confidence: 97%
See 2 more Smart Citations
“…The most key proteins were HSPB1 and CRYAB, which were small heat shock proteins (sHsp) that combined misfolded proteins to prevent them from denaturation, inhibited cellular apoptosis and regulated the intracellular redox state as molecular chaperones 15,16 . In mutant HSPB1 expressing motor axons, the researchers observed the decreased mitochondrial Complex I activity and increased mitochondrial vulnerability, resulted in increased superoxide release and decreased mitochondrial glutathione levels 17 . The CRYAB could protect cells from hypoxia and maintain mitochondrial integrity 18,19 and also had other roles in vascular biology 20 .…”
Section: Discussionmentioning
confidence: 99%